The use of UAV platforms for remote sensing applications: Case studies in Cyprus - Themistocleous, Kyriacos (My University, 2014)
The use of cost-effective Unmanned Aerial Vehicles (UAVs) are becoming common tools for researchers for numerous applications. Since UAVs vary in size and payload capacity, various sensors can be installed onto the platform. UAVs can be a efficient and low cost resource for remote sensing applications. Different remote sensing techniques can be used with UAVs, such as field spectroscopy, multi-spectral cameras, infrared cameras and thermal cameras. This paper examines several UAV platforms that were used by the Cyprus University of Technology for remote sensing applications in Cyprus. Using these UAV systems for different applications, the advantages and disadvantages were examined and discussed.
Keywords: Remote sensing; Spectroscopy; UAV